Subregionalism and World Order
XII, 268 p.
Keywords: Subregionalism and World Order brings together the work of a diverse range of area specialists in its treatment of sub-regional cooperation schemes. Sub-regional projects covered include the Central European Free Trade Area, the Black Sea Economic Scheme, Ecowas in West Africa, Mercosur, The Association of Caribbean States, Chilean strategies of subregional cooperation, the 'Greater China' project, Asean and the East Asian Economic Caucus. This is the first volume of its kind to embrace such a geographically diverse treatment of the subregional system. Through comparison of the various schemes it also seeks to mount a case for a 'new IPE' perspective in the understanding of subregional cooperation.